Synthesis and photophysical properties of N-alkyl dithieno[3, 2-b:2′, 3′-d]pyrrole based donor/acceptor-π-conjugated copolymers for solar-cell application. Issue 28 (15th June 2022) - Trinh, Cuc Kim; Nassar, Gamal M.; Abdo, Nabiha I.; Jung, Suhyun; Kim, Wonbin; Lee, Kwanghee; Lee, Jae-Suk
Abstract : The relationships between the structure and the property of donor–acceptor copolymers based on dithieno[3, 2- b :2′, 3′- d ]pyrrole as a strong donor unit and isoindigo or thiazole as acceptor units are successfully studied. Abstract : Two kinds of donor–acceptor π-conjugated copolymer based on poly{[ N -hexyl-dithieno(3, 2- b :2′, 3′- d )pyrrole-2, 6-diyl] alt -[isoindigo]} (PDTP-IID) and poly{[ N -hexyl-dithieno(3, 2- b :2′, 3′- d )pyrrole-2, 6-diyl] alt -[thiazol-2, 5-diyl]} (PDTP-Thz) were investigated. These copolymers were synthesized via a Stille coupling reaction. The results showed the structure–property relationships of different donor–acceptor (D–A) combinations. The polymer structures and photophysical properties were characterized by 1 H NMR, TGA, DSC, UV-vis absorption spectroscopy, AFM, CV, and XRD measurement. Through UV-vis absorption and cyclic voltammetry (CV) measurements, it showed that the copolymers exhibit not only a low bandgap of 1.29 eV and 1.51 eV but also a deep highest occupied molecular orbital (HOMO) of −5.49 and −5.11 eV. Moreover, photovoltaic properties in combination with the fullerene derivatives were investigated. The device based on the copolymers with PC71 BM exhibited higher maximum power conversion efficiency and higher maximum short-circuit current density of 0.23% with 1.64 mA cm −2 of PDTP-IID:PC71 BM and 0.13% with 1.11 mA cm −2 of PDTP-Thz:PC71 BM than those of the copolymers with PC61 BM. Measurements performed for N -hexyl-dithieno(3, 2- b :2′, 3′- d )pyrrole-based copolymers proved the potential of these polymers to be applied in optoelectronic applications.